PENGEMBANGAN MEDIA PEMBELAJARAN MENGGUNAKAN WORDWALL BERBASIS PBL PADA MATA PELAJARAN IPAS KELAS V SDN DARMOREJO 01 - Prasetyaning Windy Pramesti; Pinkan Amita Tri Prasasti; Raras Setyo Retno (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Basically, this science lesson contains a lot of material and long explanations that must be memorized. Teachers can utilize learning media simultaneously with the learning process. The main aim of this research is to develop learning media using wordwalls in science subjects. This research method is Research and Development (R&D) by applying the ADDIE model which includes analysis, design, development, implementation and evaluation. Learning media testing was carried out at SDN Darmorejo 01. The validity test of the material obtained a result of 93.3% with a very feasible category. The media validity test obtained a result of 90% with a very feasible category. The language validity test obtained a result of 97.7% in the very appropriate category. The results of the teacher questionnaire obtained results of 88% in the very good category. Then the average result of the questionnaire for 15 students was 90.8% in the very good category. Thus it can be concluded that the learning media using wordwall is good and suitable for use in schools.